How Do Maternal Gestational Diabetes and Preterm Premature Rupture of Membrane (PROM) Contribute to Neonatal Jaundice and Sepsis? A Case Report and Narrative Review - Melisa Indah Mustikasari; Aditya Fendi Uji Pamungkas; Alexander Tikara Sugondo; Made Chindy Dwiyanti Marheni Putri; Razita Aulia Azkia (Knowledge Dynamics, 2025)
Gestational diabetes mellitus (GDM) and preterm premature rupture of membranes (PPROM) are significant obstetric conditions associated with heightened maternal and neonatal morbidity and mortality. Globally, complications of preterm birth, particularly due to PPROM, account for 35% of neonatal deaths. The coexistence of GDM and PPROM compounds risks, exacerbating adverse neonatal outcomes. This report about a 21 years old primigravida at 32–34 weeks of gestation with untreated GDM and PPROM for over 12 hours. The patient presented with decreased fetal movement and was managed conservatively with corticosteroids, antibiotics, and tocolytics. However, signs of fetal distress necessitated cesarean delivery, resulting in the birth of a male neonate 2370 g, APGAR 2/3, with asphyxia, respiratory distress, and hypoglycemia. Postnatal complications included jaundice and neonatal sepsis, which required 22 days of intensive NICU care with respiratory support, dextrose infusion, and antibiotics. The neonate showed gradual improvement. The coexistence of GDM and PPROM significantly increases the risk of adverse neonatal outcomes such as respiratory distress, hypoglycemia, jaundice, and sepsis. Early diagnosis, glycemic control, prophylactic antibiotics, and administration of corticosteroids are critical to improving maternal and neonatal outcomes. This case underscores the importance of a multidisciplinary approach and further research to refine best practices in managing GDM complicated by PPROM.